1974
DOI: 10.1037/h0037272
|View full text |Cite
|
Sign up to set email alerts
|

Structured and nonstructured human relations training.

Abstract: Participant perceptions following structured and nonstructured human relations training were investigated. The design included three structured and three nonstructured groups and three leader teams with each team conducting one group under each of the two formats. The Group Opinion Questionnaire was administered to participants at the twelfth (final) session. Participants in structured groups reported greater ego involvement in their groups, more self-perceived personality change since joining the group, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…How well debriefers are trained in the structure and process of a debriefing will determine their ability to lead the group. Greater experience in group leaders is associated with more favorable participant perceptions (Levin & Kurtz, 1974). From the presentation so far, it is apparent that the background, training and personal qualities of the leader are extremely important variables in making successful debriefings.…”
Section: Leadership Atid Processmentioning
confidence: 99%
“…How well debriefers are trained in the structure and process of a debriefing will determine their ability to lead the group. Greater experience in group leaders is associated with more favorable participant perceptions (Levin & Kurtz, 1974). From the presentation so far, it is apparent that the background, training and personal qualities of the leader are extremely important variables in making successful debriefings.…”
Section: Leadership Atid Processmentioning
confidence: 99%
“…Gormally (1975). Levin and Kurtz (1974). and Wilbur et al ( 198 I), group effectiveness may be improved through increased structure.…”
Section: Discussionmentioning
confidence: 99%
“…In extended human relations training groups that were either structured (that is, utilized structured exercises) or nonstructured (that is, traditional sensitivity training with no exercises), Levin and Kurtz (1974) found that structure did result in more ego involvement, perceived personality change and group unity (cohesion). While it is difficult to compare Lee and Bednar (1977) and Levin and Kurtz (1974), two points can be made.…”
Section: Group Contracts and Initial Group Structurementioning
confidence: 99%
“…While it is difficult to compare Lee and Bednar (1977) and Levin and Kurtz (1974), two points can be made. First, the positive impact of structure in Levin and Kurtz may be a function of the flexibility in the implementation group structure.…”
Section: Group Contracts and Initial Group Structurementioning
confidence: 99%
See 1 more Smart Citation